Paravertebral Burkitt's Lymphoma in a Child: An Unusual Presentation. (24th November 2012) - Hoyoux, C.; Forget, P.; Piette, C.; Dresse, M. F.; Florkin, B.; Rausin, L.; Thiry, A.
Abstract : Paravertebral malignant tumors constitute 4.8% of cancer cases in pediatric oncology and are mostly composed of neuroblastoma (46.4%) and soft tissue sarcomas (35.7%). We describe the case of a Caucasian 6-year-old boy who was admitted for middle back pain radiated to limbs and progressively increasing weakness of the legs, suggesting a spinal cord disease. The exploration revealed two paravertebral masses extending through the neural foraminae into the epidural space. The association with elevated serum neuron specific enolase suggested at first the diagnosis of neuroblastoma, but the pathological examination revealed a Burkitt's lymphoma. This is a rare location of sporadic Burkitt's lymphoma with neurologic syndrome as first symptoms.